2012
DOI: 10.1124/mol.112.081307
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Distinct C-Terminal Domains of the Human Hydroxycarboxylic Acid Receptor-2 That Are Essential for Receptor Export, Constitutive Activity, Desensitization, and Internalization

et al.

Abstract: The human hydroxycarboxylic acid receptor 2 (HCA 2 ), also known as GPR109A and HM74a, was first identified as a niacin receptor and has recently received significant attention because of its potential to clinically modify plasma lipids in a favorable manner. Our recent studies have demonstrated that the niacin-induced internalization of HCA 2 receptors is regulated by G protein-coupled receptor kinase (GRK) 2 and arrestin3 and that internalized receptors rapidly recycle back to the cell surface. The investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…An insulin-NiAc synergy is not just a theoretical possibility but was in fact seen in our previous hyperinsulinemic clamp studies (10). Although and insulin are mediated via adipocyte cAMP lowering, but their combined effects are theoretically synergistic with NiAc, decreasing cAMP formation (28), and insulin, ligand-induced GPR109A desensitization and internalization) (34). Second, excessive exposures can invoke additional complicating mechanisms beyond FFA lowering.…”
Section: Discussionmentioning
confidence: 99%
“…An insulin-NiAc synergy is not just a theoretical possibility but was in fact seen in our previous hyperinsulinemic clamp studies (10). Although and insulin are mediated via adipocyte cAMP lowering, but their combined effects are theoretically synergistic with NiAc, decreasing cAMP formation (28), and insulin, ligand-induced GPR109A desensitization and internalization) (34). Second, excessive exposures can invoke additional complicating mechanisms beyond FFA lowering.…”
Section: Discussionmentioning
confidence: 99%
“…Given the apparent association rs61745752 with cancer metastasis, we sought to determine functional consequence of the variant which causes a truncation after amino acid 335 (E336X). Mutations in the c-terminal tail of GPCRs can have a number of consequences including loss of desensitization, and inactivation (Li et al, 2012) . GPCR desensitization is modulated through beta-arrestin binding to domains that are defined by GIRK phosphorylation (Ahn et al, 2003;Luttrell and Lefkowitz, 2002;Sente et al, 2018) .…”
Section: Resultsmentioning
confidence: 99%
“…Using a number of C-terminal deletion mutants of the hGLP-1R, this study determined residues 411e418 are critical for newly synthesised hGLP-1R cell surface expression. The membrane proximal region of the C-terminal domain is important for the biosynthetic trafficking of many GPCRs such as a 2B -AR, AT 2 R type 1A and dopamine receptor 1 (D1R) to the plasma membrane (Li et al, 2012). The membrane proximal region of the C-terminal domain of the a 2B -AR and AT 2 R type 1A (Duvernay et al, 2004) have been shown to be essential for exportation of the receptor from the ER.…”
Section: Discussionmentioning
confidence: 99%